The Application of Green Management Accounting in Supporting Sustainability: A Case Study of the Banking Sector in Indonesia - Ummi Kalsum Mutmainnah; Magdalena Pazizi; Muhammad Tavif Al Muzacky; Mukhtaruddin Mukhtaruddin (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The purpose of this study is to examine how Indonesia's banking industry uses Green Management Accounting (GMA) to promote sustainability. The banking industry must prioritize social and environmental factors in addition to financial performance as environmental concerns and the need for sustainable business practices increase. Using case studies of various Indonesian banks that have adopted sustainability principles, a qualitative research methodology was used. Reviews of the literature, examination of sustainability reports, and documentation pertaining to GMA practices were used to gather data. According to the findings, GMA implementation in the banking industry entails resource efficiency, environmental cost disclosure, and the incorporation of eco-friendly policies into operations and finance. This implementation contributes to enhancing transparency, cost efficiency, and corporate reputation in supporting sustainability. However, challenges remain, such as limitations in reporting standards and a lack of internal understanding regarding the GMA concept. Therefore, a stronger commitment, along with the development of regulations and human resource capacity, is needed to optimize the implementation of GMA in the Indonesian banking sector.